2008
DOI: 10.1016/j.neulet.2008.08.075
|View full text |Cite
|
Sign up to set email alerts
|

Use of calcium imaging for analysis of neuronal gap junction coupling

Abstract: We recently used western blots for connexin 36 and neuronal dye coupling with neurobiotin to measure developmental decrease in neuronal gap junction coupling in cell cultures. To ask whether Ca 2+ imaging also can be used to measure changes in the amount of neuronal gap junction coupling, we defined a Ca 2+ coupling coefficient as the percentage of neurons with bicuculline-induced increases in intracellular Ca 2+ that are suppressed by blocking gap junctions. We demonstrate in rat and mouse hypothalamic neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…i increase in neurons has been reported in the central nervous system, and it has been suggested that bicuculline blocks inhibitory inputs from GABAergic synapses via GABA A receptors, thus causing neuronal [Ca 2? ] i to increase (Arumuga et al 2008;Kato-Negishi et al 2003). It is known that GABA is released by two distinct mechanisms: Ca 2?…”
Section: Effect Of Endogenous Gaba In Ngmentioning
confidence: 99%
“…i increase in neurons has been reported in the central nervous system, and it has been suggested that bicuculline blocks inhibitory inputs from GABAergic synapses via GABA A receptors, thus causing neuronal [Ca 2? ] i to increase (Arumuga et al 2008;Kato-Negishi et al 2003). It is known that GABA is released by two distinct mechanisms: Ca 2?…”
Section: Effect Of Endogenous Gaba In Ngmentioning
confidence: 99%